The Effect of Task-Based Language Teaching On Students’ Reading Comprehension of Tenth Grade of SMK Putra Anda Binjai Students In Academic 2018/2019 - Juliantina Sebayang (English Teaching and Linguistics Journal (ETLiJ), 2020)
This study deals with the effect of applying task based language teaching on the students’ reading comprehension. It was conducted by using experimental research design. The population of this research was the tenth grade students of SMK Putra Anda Binjai. The sample of research were two classes which consisted of experimental group and control group which were chosen  by random sampling. Twenty eight students were taken as the samples in each class. The experimental group was taught by using task based language teaching, while the control class was taught without using task based language teaching. The data were analyzed by using t-test. The calculation shows that t-observed (2.49) was higher than t-table (1.67) at the level of significance (α) 0.05 with the degree of freedom (df) 54. The result is hypothesis stated that there is significantly effect of applying task based language teaching on the tenth grade students’ reading comprehension is accepted.